Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Pancasila Kebiasaan Hidupku di Kelas V SDN Model Mataram - Rahayu, Astuti; Nisa, Khairun; Supriatin, Dwi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The purpose of this study is to determine the improvement of students’ critical thinking skills on the topic Pancasila: My Daily Habits through the implementation of the Problem-Based Learning (PBL) model in Class V of SDN Model Mataram. This research is a Classroom Action Research (CAR) using the Kurt Lewin model. The subjects of the study were 22 fifth-grade students of SDN Model Mataram. Data collection techniques included tests, observations, and documentation. The results of the study show that the application of the Problem-Based Learning model can improve students’ critical thinking skills on the topic Pancasila: My Daily Habits. This is evident from the gradual increase in students’ learning outcomes in each cycle, with an average critical thinking score of 81.33 in Cycle II compared to 52.02 in Cycle I, showing a difference of 29.33 points. The post-test results showed a significant improvement compared to the pre-test results. These findings indicate that the implementation of the Problem-Based Learning model is highly effective in enhancing students’ critical thinking skills on the topic Pancasila: My Daily Habits in Class V of SDN Model Mataram.